Study of two-dimensional Flow around the NACA 0009 Airfoil using CFD - صالح, ايهاب (Latakia University Journal -Engineering Sciences Series, 2024)
The use of numerical methods to solve the flow equations helps in analyzing many physical phenomena related to the nature of flow, and their use has become possible after the tremendous development in the computer industry in terms of speed and storage capabilities. Therefore, investing in the numerical modeling loop played a major role from a design and operational perspective. This research analyzes the two-dimensional flow around an airfoil using the Computational Fluid Dynamics (CFD) available in the Ansys-Fluent program, where the URANS method and the turbulence model were used to close the system of equations. The study model is a two-dimensional model of an airfoil, which is a NACA 0009. The two-dimensional flow around the airfoil section with different angles of attack was studied, and both the velocity and pressure fields around the airfoil were analyzed.